"The First Mark of Pain": Toward a child‐centered methodological reorientation of social theory, race and corporal punishment in American life. Issue 12 (10th November 2021) - Patton, Stacey; Rollo, Toby; Curry, Tommy J.
Abstract: The current white supremacist racial order in America fundamentally relies on fear and pain to shape the subjectivities of Black people in childhood. This violence is most visible when enacted by police officers against unarmed Black youth. A less visible yet more pernicious form of racist violence against Black children is exercised by community proxies such as Black teachers and parents. Annual government reports reveal that Black children are more likely to be injured or killed by their parents than by police. In this paper we inquire as to why, despite the many Black writers who have described parental violence as an intergenerational re‐enactment of the violence of slavery, and despite decades of research on the harms of hitting children, social theorists have not analyzed how Black parents can serve as proxies for white supremacist violence. We argue that Black parenting culture has in many ways internalized the white supremacist view that corporal punishment is required to instill the discipline necessary to spare Black youth from police violence and incarceration. We conclude that until social scientists foreground the voices of Black youth in their studies, rather than adults, our ability to understand and confront the reproduction of white supremacist violence will be impeded. We argue that the physical punishment of children in Black families is an aspect of the legacy or "afterlife" of slavery. We contend that this omission persists because Black youth voices are absent from social analysis on the issue of physical punishment, existing only in clinical studies divorced from macro‐sociological analysis, and we discuss how this omission occurred as a matter of scholarly history.